Understanding Clementi’s Fingerings - Zafeiropoulos, Anastasios (2023)
Presentation of doctoral research and workshop on historical fingerings
FRIS
0
Keywords: Declassifying the Classics: Rhetoric, Technology, and Performance, 1750-1850